The transition to renewable energy - Owen, Anthony David (Routledge, 2004)
This impressive new collection couldn't come at a better time. With global warming now becoming physically noticeable and the Kyoto treaty stalling in its efforts to get the developed world on board, to take a look at the economic factors of global warming is very much welcome. With contributions from distinguished authors and covering everything you need to know about global warming and its financial implications, this readable book will appeal across the political and scientific spectrum.